DAMPAK KEGIATAN MEETING, INCENTIVE, CONVENTION AND EXHIBITION (MICE) TERHADAP DEVISA NEGARA - Suhartono Suhartono (Universitas Bina Sarana Informatika, 2011)
MICE Industry plays an important role in world tourism, because of the impact of theimplementation of a MICE event has a multiplier effect (multiplier effect) for other areas of life.MICE events not only generate income for those who deal directly with any MICE event, butindirectly also involve many other economic actors. The economic impact of MICE activities arevery big influence on the increase in foreign exchange and other sectors. So the MICE industry isa very promising source of income and many countries that make the MICE industry as the mainsource of income for his country.Keywords: Impact, MICE, Foreign Exchang